MicroRNA 138 Upregulation is Associated with Decreasing Levels of CCND1 Gene Expression and Promoting Cell Death in Human Prostate Cancer Cell Lines - Nasrin Haghighi-Najafabadi; Shima Fayaz; Mahboubeh Berizi; Ghazal Haddad; Pezhman Fard-Esfahani (Tabriz University of Medical Sciences, 2023)
Background: This research intended to discover the significance of miR-138 (microRNA 138) on the expression profile, proliferation, and the associated regulatory mechanisms in prostate cancer (PCa). Methods: Thirty-five specimens of prostate were studied to evaluate the expression level of miR138 by RT-qPCR (Quantitative reverse transcription polymerase chain reaction). Bioinformatics analysis was performed to search for the target genes of miR-138; and ABL1 (ABL proto-oncogene 1, non-receptor tyrosine kinase), CCND1 (cyclin D1), CCND3 (cyclin D3), VIM (vimentin), TWIST1 (twist family bHLH transcription factor 1), HIF1A (hypoxia-inducible factor 1 subunit alpha), and TERT (telomerase reverse transcriptase) genes were selected. Then, the biological role of miR-138 and CCND1 in the progression of PCa was investigated using RT-qPCR and luciferase reporter gene assay. Finally, overexpression of miR-138 on the proliferation in PCa cell lines was analyzed using the MTT (3-(4, 5-dimethylthiazol-2-Yl)-2, 5-diphenyltetrazolium bromide, Sigma, Germany) assay. Results: RT-qPCR showed that the expression of miR-138 downregulated in PCa tissues and cell lines. Bioinformatics analysis and RT-qPCR assay demonstrated that CCND1 expression level was negatively correlated with miR-138 in PCa tissues and the PC3 cell line. Moreover, CCND1 was predicted to be the target gene of miR138 in the PC3 cell line based on the results of luciferase reporter gene assay. Substantially, over-expression of miR138-5p mimic could inhibit the expression level of CCND1 gene in PC3 cell lines. Lastly, over-expression of miR-138 inhibited the proliferative capacities in PC3 and DU-145 cells. Conclusion: Our research introduces miR-138 as a negative regulator of CCND1 in the progression of PCa with an inhibitory impact on the proliferation rate of PCa cell lines. This regulatory mechanism could be utilized for the design and target selection of remedial miRNA-based approaches.